An Update Evolving View of Copy Number Variations in Autoimmune Diseases - Song, Rong-hua; Gao, Chao-qun; Zhao, Jing; Zhang, Jin-an (Frontiers in Genetics, 2022)
Autoimmune diseases (AIDs) usually share possible common mechanisms, i.e. a defect in the immune tolerance exists due to diverse causes from central and peripheral tolerance mechanisms. Some genetic variations including copy number variations (CNVs) are known to link to several AIDs and of importance in the susceptibility to AIDs and the potential therapeutic responses to medicines. As an important source of genetic variants, DNA CNVs has been shown to be very common in AIDs, implying these AIDs may possess possible common mechanisms. In addition, some CNVs are differently distributed in various diseases in different ethnic population, suggesting that AIDs may have their own different phenotypes and different genetic and/or environmental backgrounds among diverse populations. As the continuous advance in genotyping technology such as high throughput whole genome sequencing method, more susceptible variants have been found. Moreover, further replication studies should be conducted to confirm the results of studies with different ethnic cohorts and independent populations. In this review we aim to summarize the most relevant data emerged in the past few decades on the relationship of CNVs and AIDs and gain some new insights into the issue.